The Application of the Principle of Judges’ Independence in Blasphemy Cases in Indonesia's Post-Reform Era - Maula, Bani Syarif; Ariyanti, Vivi (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This research departs from a paradigm that the freedom of judges is a form of court independence, which requires that decisions taken must consider objectivity without pressure from any party. This study focuses on the attitude of judges' independence from factors that can influence court decisions, both internal and external factors related to the interests of certain groups. Based on these problems, this study addresses the issue of the independence of judges in cases of blasphemy. This type of research is empirical normative with a qualitative descriptive approach. The data sought for this research is data that comes from the facts of the application of material and formal law by judges in court. In addition, this data is also strengthened by interviews. This study concludes that the analysis of the application of the blasphemy article proves that judges as law enforcers have difficulty translating the substance of blasphemy because of the unclear formulation of Article 156a letter 'a' of the Indonesian Criminal Code. The judge's decision in the blasphemy case does not reflect the independence values of the judges who decide the case. Judges in making decisions on cases handled must be based on their ability to think and will freely (independently) but within the limitations of responsibility and objectivity. The panel of judges in blasphemy cases tends to adopt a more general and situation-oriented attitudes.